2018
DOI: 10.1016/j.scitotenv.2017.10.171
|View full text |Cite
|
Sign up to set email alerts
|

Dung beetles as drivers of ecosystem multifunctionality: Are response and effect traits interwoven?

Abstract: Rapid biodiversity loss has emphasized the need to understand how biodiversity affects the provisioning of ecological functions. Of particular interest are species and communities with versatile impacts on multiple parts of the environment, linking processes in the biosphere, lithosphere, and atmosphere to human interests in the anthroposphere (in this case, cattle farming). In this study, we examine the role of a specific group of insects - beetles feeding on cattle dung - on multiple ecological functions spa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 54 publications
0
27
0
2
Order By: Relevance
“…Recent studies in the Atlantic forest (and in neotropical forests in general) have shown that land uses with complete loss of the canopy cover show a marked reduction in dung beetle abundance and diversity 2,3,5,65 and that those preserving the canopy cover (at least partially) are often used by native forest dung beetles 2,3,5,7,66,67 . While these differences have been explained by the hypothesis of physiological restrictions (particularly the tolerance to high temperatures) 3,5,14 , the results of this study are the first direct evidence to suggest that the thermal niche might be one of the main determinants of the ability of forest dung beetles to colonize open areas.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…Recent studies in the Atlantic forest (and in neotropical forests in general) have shown that land uses with complete loss of the canopy cover show a marked reduction in dung beetle abundance and diversity 2,3,5,65 and that those preserving the canopy cover (at least partially) are often used by native forest dung beetles 2,3,5,7,66,67 . While these differences have been explained by the hypothesis of physiological restrictions (particularly the tolerance to high temperatures) 3,5,14 , the results of this study are the first direct evidence to suggest that the thermal niche might be one of the main determinants of the ability of forest dung beetles to colonize open areas.…”
Section: Discussionmentioning
confidence: 69%
“…Differences in dung beetle diversity among land uses differing in canopy cover have been associated mainly with a marked increase in ground level temperature 2 , 8 – 10 and with the low tolerance of forest dung beetles to high temperatures (typical of open habitats during the day) 3 , 11 – 13 . Although previous studies have suggested that the physiological intolerance of forest dung beetles to high temperatures is a potential constraint to exploit disturbed habitats 2 , 3 , 14 , this hypothesis has never been tested. This knowledge gap on dung beetle thermal biology led us to ask the following question: can the thermal niche of dung beetles explain the occupation of disturbed habitats, and taxonomic and functional changes reported in previous studies?…”
Section: Introductionmentioning
confidence: 99%
“…This may explain the strong differences in dung removal between habitats due to the strongly changing abundance of large tunnellers in our study area. In Scandinavia, functionally important species suffered from disproportionate declines (Piccini et al, 2018) and this may also have occurred in Central Europe. High densities of dung beetles with low individual functional importance can support equivalent levels of functioning as provided by species with high individual functional importance .…”
Section: Discussionmentioning
confidence: 99%
“…A general positive link between biodiversity and ecosystem functioning (Allan et al, 2015;Butterfield, Camhi, Rubin, & Schwalm, 2016) has been variously ascribed to the effects of diversity per se (e.g., more species complement each other's use of available resources, thus allowing more complete resource use; e.g., Tilman et al, 2001) versus effects of species identity (with some species being particularly efficient from a functional perspective; e.g., Cardinale, Palmer, & Collins, 2002;Hooper, Chapin, & Ewel, 2005). Overall, species within a community often have varying impacts on individual ecosystem functions (Cardinale et al, 2006;Piccini et al, 2018;Slade et al, 2017).…”
Section: Introductionmentioning
confidence: 99%